Hysteresis Based Fsk Modulation for Visible Light Communication - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2020)
In this paper it is shown a way to perform a customized FSK modulation scheme suitable for multiuser Visible Light Communication (VLC). A hysteresis band current controller is simulated at the power stage for modulate the LED current using the FSK modulation as reference. A digital filter based demodulation scheme is presented also, in order to recovering the information contained in the LED current. Finally, simulation results are presented for validate the proposed schemes. © 2020 IEEE.